Pemahaman Santri Terhadap Nilai-Nilai Pancasila - Fatiyah Fatiyah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2017)
The goals of this research are to describe and to analyze the colleger Santris’ understanding about Pancasila ideology (1) in averting fundamentalism and (2) on tolerance values.Based on the study and the center of attention of this research, it is a qualitative research. The subjects are the collegers of Adab dan Ilmu Budaya Faculty of UIN Sunan Kalijaga Yogyakarta with background as Santris.The data collection techniques use some methods, i.e.: interview, observation, and documentation. The data analysis consists of three phases, i.e.: (1) data reduction, (2) data display, and (3) conclusion drawing/verification, is usually known as interactive model of analysis.The results are that the understanding of colleger Santris of Adab dan Ilmu Budaya Faculty about Pancasila (1) in overall they know less, either in general or detail, but they understand the role of Pancasila as a State Fundamental Norm, i.e. as a unifier of the nation diversity in culture, ethnic, and religion; (2) on tolerance values, it is understood as a harmony among the different religious adherents as the main principle for Santris to understand the values of Pancasila as the noble cultural values of the nation.